FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI USAHA TANI BAWANG MERAH DI DESA BARENG KECAMATAN SEKAR KABUPATEN BOJONEGORO - Warjito, Warjito; Kustanti, Asihing; Syafrial, Syafrial (Agros Journal of Agriculture Science, 2024)
Mastery of Information and Communication Technology (ICT) has a significant role in developing the agricultural sector, especially in increasing efficiency and productivity. This research aims to investigate the influence of ICT mastery on shallot farming in Bareng Village, Bojonegoro Regency. Through a quantitative approach and collecting primary and secondary data from 93 respondents, multiple regression analysis shows that mastery of ICT makes a positive and significant contribution to agricultural development. Apart from that, factors such as the amount of fertilizer and type of seed also influence production. This study highlights the importance of integrating ICT in agricultural practices to increase efficiency, optimize production and strengthen the competitiveness of agricultural products in the global market. The results of this research provide important insights for policy makers, farmers and other stakeholders in understanding the role of ICT in facing challenges and exploiting opportunities in agricultural development.